Two new nematode species of the genus Paratrilobus Micoletzky, 1922 (Nematoda, Triplonchida) from the water area of Lake Baikal (Russia) - Naumova , Tatyana V.; Gagarin , Vladimir G. (European Journal of Taxonomy, 2020)
This paper describes and illustrates two new nematode species of the genus Paratrilobus Micoletzky, 1922. The species Paratrilobus tankhoyensis sp. nov. was found at the estuary of the Pereyomnaya River (water area of Lake Baikal, near the Tankhoy railway station). Paratrilobus tankhoyensis sp. nov. is most similar to P. expugnator (Tsalolichin, 1976) in the body size, but differs in the comparatively thin body, shorter and thicker tail, shorter stoma and spicules. Another new species, Paratrilobus aquaticus sp. nov., was found in Posolsk Bank (natural underwater elevation of the bottom between the southern and central basins of Lake Baikal). The species is similar to P. granulosus Gagarin & Naumova, 2011 and P. ultimus (Tsalolichin, 1977) in the structure of the precloacal supplements. It differs from the former in the absence of crystalloids, a comparatively longer pharynx, longer stoma and outer labial setae as well as the absence of subterminal seta. It differs from the latter in a longer pharynx, stoma and longer outer labial setae as well as a longer and more slender tail. We also discuss diagnostic features of the males of the genus Paratrilobus.